Method for testing the anti-bioadhesion properties of an antifouling material

CN122982902APending Publication Date: 2026-10-27ANHUI TRANSPORTATION VOCATIONAL & TECH COLLEGE
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410757162.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-06-13
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0010]现有的防污材料抗生物粘附性能测试方法在进行测定时,其测试并非处于相似环境,不能真实有效地测定样品的防污性能,且操作繁琐,实验周期长;且不适用于内河和海洋中的大部分生物

Benefits of technology

[0025]与现有技术相比,本发明提供的一种防污材料抗生物粘附性能测试方法,通过对比模拟生物粘液粘附强度和生物自身粘附强度的剪切力参数,可以方便快捷地显示出防污材料的抗生物粘附性能,若模拟生物粘液粘附强度大于生物自身粘附强度的剪切力参数,则表明该防污材料抗生物粘附性能较差;反之,则表明该防污材料抗生物粘附性能较强;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122982902A_ABST
    Figure CN122982902A_ABST
Patent Text Reader

Abstract

The application discloses a kind of anti-fouling material anti-bioadhesion performance test methods, it is related to anti-fouling material performance test technical field, including sample preparation, adhesion test, tensile test, calculate simulation biological mucilage adhesion strength and evaluate anti-fouling material anti-bioadhesion performance;The anti-fouling material anti-bioadhesion performance test method, by comparing the shear force parameters of simulation biological mucilage adhesion strength and biological own adhesion strength, the anti-bioadhesion performance of anti-fouling material can be conveniently and quickly displayed, if simulation biological mucilage adhesion strength is greater than the shear force parameters of biological own adhesion strength, then indicate that the anti-bioadhesion performance of anti-fouling material is poor;Conversely, then indicate that the anti-bioadhesion performance of anti-fouling material is strong;Test method is simple, convenient to operate, cost is lower, process demand degree is low;It can be suitable for testing the anti-bioadhesion performance of anti-fouling material in different medium environments, applicability is wider, representativeness is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to performance testing technology for antifouling materials, specifically to a method for testing the antifouling properties of antifouling materials against bioadhesion. Background Technology

[0002] Bioadhesion is the process by which organisms (such as bacteria, algae, plankton, etc.) attach to a solid surface. This attachment usually occurs in water or other liquid media, but it can also occur on solid surfaces in the air. Bioadhesion is a complex process involving a variety of factors, including the characteristics of the organism and the surface, as well as the properties of the medium.

[0003] Bioadhesion can pose a variety of hazards, especially in the marine sector, including:

[0004] Increased drag and fuel consumption: Biofouling on the surface of a ship increases water friction, leading to increased drag and thus increased fuel consumption; it also slows down the ship's speed, extends its range, and affects sailing efficiency.

[0005] Increased maintenance costs: Bioadhesion can corrode ship surfaces, accelerate hull aging and damage, increase maintenance and repair costs, reduce ship lifespan and value, and increase downtime and operating costs.

[0006] Impact on ship stability: Bioadhesion increases the surface weight of a ship, changes the ship's center of gravity, affects the ship's stability, increases the risk of capsizing, and poses a threat to navigation safety.

[0007] Spread of harmful organisms and diseases: Bioadhesion may carry harmful organisms, pathogens or parasites, which may spread diseases and harm the ecological environment and human health.

[0008] To reduce the harm caused by bioadhesion, common measures include the application of antifouling coatings. Applying special antifouling materials can reduce bioadhesion; however, experimental research on the antifouling properties of these materials is still in its early stages, with no mature theoretical results and no dedicated instruments for experimental investigation. Although atomic force microscopy (AFM) can directly measure the forces between biomolecules, its high cost makes it unsuitable for large numbers of research samples.

[0009] Chinese invention patent CN106501132B discloses a method for testing the biofouling resistance of antifouling materials. This method involves experimentally testing the contact angle and roll-off angle of 6-10 groups of aqueous solutions of bioadhesives with different concentrations. The contact angle and roll-off angle of the bioadhesive on the surface of the test material are calculated by linear fitting. Then, the contact angle and roll-off angle are compared with those of a blank sample to calculate the antifouling adhesion coefficient of the test material. The antifouling adhesion coefficient is used as a parameter for comparing and evaluating the adhesion characteristics of the bioadhesive on the surface of the test material.

[0010] Existing methods for testing the antifouling properties of antifouling materials are not conducted in similar environments, making it impossible to accurately and effectively measure the antifouling performance of samples. Furthermore, these methods are cumbersome, time-consuming, and unsuitable for most organisms in inland rivers and oceans. Summary of the Invention

[0011] The purpose of this invention is to provide a method for testing the antifouling properties of antifouling materials against bioadhesion, in order to overcome the above-mentioned shortcomings in the prior art.

[0012] To achieve the above objectives, the present invention provides the following technical solution: a method for testing the antifouling performance of antibioadhesion materials, comprising the following steps:

[0013] S1. Sample preparation: Select the antifouling material to be tested, and evenly apply the antifouling material to one end of a blank plastic strip to obtain an antifouling coating strip; evenly apply Ara ldi te2011 two-component epoxy resin adhesive to one end of another blank plastic strip to obtain an epoxy resin adhesive strip; then adhere the epoxy resin adhesive strip, coating side down, to the end of the antifouling coating strip coated with antifouling material.

[0014] S2. Adhesion test: After the antifouling coating strip and epoxy resin strip are firmly adhered, an adhesion test is conducted on the environmental medium in which the antifouling material is applied.

[0015] S3. Tensile test: Use a tensile testing machine to perform a tensile test on the sample treated in S2, and record the relevant experimental data;

[0016] S4. Calculate the simulated biological slime adhesion strength: Process the relevant experimental data described in S3 to obtain the simulated biological slime adhesion strength.

[0017] S5. Evaluate the antifouling properties of the antifouling material against bioadhesion: Compare and analyze the shear force parameters of the simulated bio-slime adhesion strength obtained in S4 with the bio-adhesion strength of the organism itself to evaluate the antifouling properties against bioadhesion.

[0018] Furthermore, the antifouling material described in S1 is a hydrogel or resin-based antifouling material.

[0019] Furthermore, the environmental medium for the application of the antifouling material described in S2 includes inland river water, seawater, or air, and the adhesion test required in S2 is 12 hours.

[0020] Furthermore, the tensile test described in S3 includes the following steps:

[0021] S31. Clamp the plastic strip and the anti-fouling coating at the top and bottom ends of the tensile testing machine respectively;

[0022] S32. Set the tensile testing machine to a tensile testing speed of 50 mm / min, stretch the sample after the treatment in S2, and record the maximum stress during the stretching process.

[0023] Furthermore, the calculation formula for the data processing described in S4 is as follows: In the calculation formula, N is the average value of the maximum stress, and S is the area of ​​the adhesion region. Substituting the average value of the maximum stress into the calculation formula, the maximum shear strength K is calculated, and K is the simulated biological slime adhesion strength.

[0024] Furthermore, the smaller the shear force parameter of the simulated biological slime adhesion strength compared to the biological self-adhesion strength described in S5, the stronger the antifouling material's anti-bioadhesion performance; conversely, the smaller the parameter, the weaker the antifouling material's anti-bioadhesion performance.

[0025] Compared with existing technologies, the present invention provides a method for testing the antifouling properties of antifouling materials. By comparing the shear force parameters of simulated biofilm adhesion strength and biofilm adhesion strength, the antifouling properties of antifouling materials can be conveniently and quickly displayed. If the simulated biofilm adhesion strength is greater than the shear force parameter of biofilm adhesion strength, it indicates that the antifouling material has poor antifouling properties; conversely, it indicates that the antifouling material has strong antifouling properties.

[0026] This test method is simple, easy to operate, low in cost, and requires minimal processing. The adhesion strength of the Ara ld ite2011 two-component epoxy resin adhesive is greater than that of adult barnacles, indicating high representativeness. This test method is applicable to testing the antifouling properties of antifouling materials in different media environments and has wide applicability. Attached Figure Description

[0027] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in this invention. For those skilled in the art, other drawings can be obtained based on these drawings.

[0028] Figure 1This is a schematic diagram of the preparation of a single sample provided in an embodiment of the present invention;

[0029] Figure 2 This is a schematic diagram of the adhesion test of some samples in air medium provided in the embodiments of the present invention;

[0030] Figure 3 This is a schematic diagram illustrating the adhesion test of some samples in an inland river medium provided in an embodiment of the present invention;

[0031] Figure 4 This is a schematic diagram of a tensile testing machine device provided in an embodiment of the present invention;

[0032] Figure 5 Morphology images of some samples after adhesion testing provided in embodiments of the present invention (the numbers in the images represent the percentage of hydrogel added);

[0033] Figure 6 Maximum shear stress curves of antifouling coatings with different amounts of hydrogel added, provided in embodiments of the present invention;

[0034] Figure 7 Macroscopic morphology diagrams of antifouling coatings with different amounts of hydrogel added, provided in embodiments of the present invention. Detailed Implementation

[0035] To enable those skilled in the art to better understand the technical solution of the present invention, the present invention will be further described in detail below with reference to the accompanying drawings.

[0036] Example:

[0037] Please see Figures 1-7 A method for testing the antifouling properties of antifouling materials against bioadhesion includes the following steps:

[0038] S1. Sample preparation: Hydrogel / organosilicon composite coating was selected as the antifouling material for testing. In this embodiment, five hydrogel / organosilicon composite coatings with different amounts of hydrogel were prepared by adding different amounts of hydrogel to the organosilicon for testing. The amounts of hydrogel added were 0%, 10%, 20%, 30%, and 40%.

[0039] A hydrogel / silicone composite coating was evenly applied to one end of a 120mm × 30mm blank plastic strip, with a thickness of 2mm. Ara ldite2011 two-component epoxy resin adhesive was evenly applied to a 20mm × 20mm area on one end of another blank plastic strip to obtain an epoxy resin strip. The epoxy resin strip was then adhered to the end of the antifouling coating strip with the antifouling material applied, with the coated side facing down. At least 6 samples were prepared for each antifouling material to be tested, and they were randomly divided into two groups of 3 samples each.

[0040] In a 25°C test, the Ara ldi te2011 two-component epoxy resin adhesive, using SMC plastic as an example, achieved an average lap shear strength (ISO4587) of 8 N / mm². 2 It has a shear modulus of 1.2 GPa and a water absorption rate of less than 0.15 within 24 hours, which is greater than the adhesion value of biofouling in various inland rivers and marine environments, and is suitable for use in inland river and marine environments.

[0041] Hydrogel / silicone composite coatings are composite coatings that combine the properties of hydrogel and silicone materials. The following is a brief introduction to these two materials and their composite coatings:

[0042] Hydrogels: Hydrogels are gel systems formed by hydrophilic polymers with a three-dimensional interconnected network structure that swell but do not dissolve in water, along with water molecules. Their water absorption is closely related to the degree of cross-linking. The higher the degree of cross-linking, the lower the water absorption. The aggregated state of hydrogels is neither completely solid nor completely liquid; they can maintain a certain shape and volume under certain conditions, while solutes can diffuse or permeate from the hydrogel.

[0043] Organosilicon: Organosilicon compounds are characterized by a main chain of SiO bonds and side chains of Si-CH3. This molecular structure gives organosilicon materials high hydrophobicity, low surface energy, and good weather resistance. Furthermore, organosilicon possesses excellent properties not found in general organic polymers, such as good cold resistance, heat resistance, oxidation resistance, and electrical insulation.

[0044] Hydrogel / silicone composite coatings combine these two materials to form a composite coating with dual advantages. This composite coating has the following characteristics:

[0045] Excellent hydrophilicity and water retention: Due to the introduction of hydrogel, the composite coating has excellent hydrophilicity and water retention, and can absorb and retain a large amount of water, thereby improving the hydrophilicity of the coating in application.

[0046] Good thermal stability and weather resistance: Due to the introduction of organosilicon, the composite coating has good thermal stability and weather resistance, can be used in a wide temperature range, and resists the effects of various environmental factors on the coating.

[0047] Special physical and chemical properties: Depending on the specific application requirements, the ratio and type of hydrogel and organosilicon can be adjusted to give the composite coating special physical and chemical properties, such as self-healing and antibacterial properties.

[0048] Overall, hydrogel / organosilicon composite coating is a novel composite coating with excellent performance. In this embodiment, the optimal amount of hydrogel added to hydrogel / organosilicon composite coating in inland waterway and air media was explored by testing the anti-bioadhesion performance of hydrogel / organosilicon composite coatings with different amounts of hydrogel.

[0049] S2. Adhesion Test: After the antifouling coating strip and epoxy resin strip are adhered, appropriate pressure is applied to the adhesion point. One group of samples undergoes air-medium adhesion for 12 hours. Figure 2 As shown; another group of samples were immersed in inland river water for 12 hours for adhesion.

[0050] The time required for air adhesion and inland water immersion adhesion is the longest time required to simulate the protein adsorption process of fouling organisms on the substrate surface, and also the shortest time required for Ara ldite2011 two-component epoxy resin to fully cure on the antifouling material surface.

[0051] Applying appropriate pressure at the adhesion point can be achieved by pressing down with a small iron block. Stacking iron blocks together makes the epoxy resin adhesive adhere more firmly, mainly because pressure plays a key role in the epoxy resin adhesive bonding process. The specific reasons are as follows:

[0052] Increasing the contact area: Applying pressure can make the contact between the iron block and the epoxy resin adhesive more compact, thereby increasing the contact area between the two. This helps the epoxy resin adhesive to better wet and penetrate the surface of the iron block, forming a wider contact and stronger adhesion.

[0053] Eliminating air bubbles and voids: Air bubbles and voids are common problems in the adhesive process. These air bubbles and voids weaken the adhesive effect. By applying pressure, these air bubbles and voids can be forced out, making the epoxy resin glue and the iron block form a tighter contact, thereby improving the adhesion strength.

[0054] Promoting the curing reaction: The curing of epoxy resin adhesive is a chemical reaction process that requires cross-linking and reaction between molecules. Applying appropriate pressure can help promote this curing reaction, allowing the epoxy resin adhesive to form a three-dimensional cross-linked structure more quickly, thereby improving its adhesion and durability.

[0055] Improving adhesive layer uniformity: If the adhesive layer thickness is uneven during the bonding process, it may lead to inconsistent adhesion force. By applying pressure, the adhesive layer can be subjected to appropriate pressure in the vertical direction, thereby making the adhesive layer more uniform. This helps to ensure that the entire adhesive area is subjected to uniform adhesion force, thus improving the overall adhesion effect.

[0056] In summary, pressing an iron block can make epoxy resin adhesive adhere more firmly, mainly because pressure can increase the contact area, eliminate air bubbles and voids, promote the curing reaction, and improve the uniformity of the adhesive layer. These factors work together to make the adhesion between epoxy resin adhesive and iron block stronger.

[0057] S3. Tensile test: Clamp the plastic strip and the anti-fouling material coating at the top and bottom of the tensile testing machine respectively. Set the tensile testing machine to a tensile speed of 50 mm / min. Stretch each sample after S2 treatment, record the maximum stress during the stretching process, and calculate the average value of the maximum stress for each group of samples.

[0058] S4. Calculate the simulated biological slime adhesion strength: Substitute the average value of the maximum stress of each group of samples obtained in S3 into the calculation formula. In the calculation formula, N is the average value of the maximum stress of each group of samples, S is the area of ​​the adhesion region, and the maximum shear strength K (kPa) calculated by the calculation formula is the simulated biological mucus adhesion strength.

[0059] This step estimates the physical quantities required to disrupt the adhesion between fouling organisms and the substrate. The benefits of this estimation are mainly reflected in the following aspects:

[0060] Preventing biofouling: Understanding the necessary physical quantities can help us design more effective prevention strategies to stop biofouling from forming. For example, if we know that a certain pressure or shear force can disrupt the adhesion of fouling organisms, then we can use these parameters to design surface coatings for ship hulls or underwater structures, giving them self-cleaning capabilities or enhancing their antifouling performance.

[0061] Maintenance cost control: Biofouling not only affects aesthetics but may also lead to a decline in structural performance and increase maintenance costs. By estimating the physical amount required to break up adhesion, maintenance strategies can be optimized, such as using more efficient cleaning methods or selecting appropriate maintenance frequencies, thereby reducing maintenance costs.

[0062] Materials science research: Predicting adhesion forces helps advance materials science research. Understanding which material properties (such as surface energy, roughness, hardness, etc.) affect adhesion forces can guide the development of new materials to meet specific anti-fouling requirements.

[0063] Environmental protection: The removal of fouling organisms usually involves the use of chemical cleaning agents, which can have a negative impact on the aquatic environment; breaking down the adhesion through physical methods (such as high-pressure water jets, ultrasound, etc.) can reduce environmental pollution; estimating the physical quantities required to break down bioadhesion can help optimize the parameter settings of these physical methods, achieving more environmentally friendly fouling removal.

[0064] Engineering design optimization: In the design of ships, underwater pipelines, offshore platforms and other engineering projects, it is crucial to consider the impact of biofouling. By estimating the physical quantities required to break adhesion, the need for antifouling can be taken into account in the design phase, and more suitable materials, coatings or structural designs can be selected, thereby improving the durability and reliability of the project.

[0065] Prediction and assessment: Estimating adhesion force helps predict the development trend and severity of biofouling, thus enabling early intervention. In addition, for existing biofouling, measuring its adhesion force can assess the difficulty and effectiveness of its removal, providing a reference for subsequent removal work.

[0066] In summary, predicting the physical quantities required to disrupt the adhesion between biofouling organisms and the substrate has many benefits, including preventing biofouling, reducing maintenance costs, advancing materials science research, protecting the environment, optimizing engineering design, and predictive assessment.

[0067] S5. Evaluate the antifouling properties of the antifouling material against bioadhesion: Compare and analyze the shear force parameters of the simulated bio-slip adhesion strength obtained in S4 with the bio-adhesion strength of the bio-slippery material to evaluate its antifouling properties against bioadhesion.

[0068] The smaller the shear force parameter of the simulated biofilm adhesion strength compared to the biofilm adhesion strength, the stronger the antifouling material's resistance to bioadhesion; conversely, the larger the parameter, the weaker the antifouling material's resistance to bioadhesion.

[0069] The foregoing has only described certain exemplary embodiments of the present invention by way of illustration. Undoubtedly, those skilled in the art can modify the described embodiments in various ways without departing from the spirit and scope of the present invention. Therefore, the foregoing drawings and descriptions are illustrative in nature and should not be construed as limiting the scope of protection of the claims of the present invention.

Claims

1. A method for testing the antifouling properties of antifouling materials against bioadhesion, characterized in that, Includes the following steps: S1. Sample preparation: Select the antifouling material to be tested, and apply the antifouling material to be tested evenly to one end of a blank plastic strip to obtain an antifouling coating strip; apply Araldite2011 two-component epoxy resin adhesive evenly to one end of another blank plastic strip to obtain an epoxy resin adhesive strip; then adhere the epoxy resin adhesive strip with the coated side facing down to the end of the antifouling coating strip with the antifouling material applied. S2. Adhesion test: After the antifouling coating strip and epoxy resin strip are firmly adhered, an adhesion test is conducted on the environmental medium in which the antifouling material is applied. S3. Tensile test: Use a tensile testing machine to perform a tensile test on the sample treated in S2, and record the relevant experimental data; S4. Calculate the simulated biological slime adhesion strength: Process the relevant experimental data described in S3, and the data processing result is the simulated biological slime adhesion strength. S5. Evaluate the antifouling properties of the antifouling material against bioadhesion: Compare and analyze the shear force parameters of the simulated bio-slime adhesion strength obtained in S4 with the bio-adhesion strength of the organism itself to evaluate the antifouling properties against bioadhesion.

2. The method for testing the antifouling properties of an antifouling material against bioadhesion according to claim 1, characterized in that, The antifouling material mentioned in S1 is a hydrogel and resin-based antifouling material.

3. The method for testing the antifouling properties of an antifouling material against bioadhesion according to claim 1, characterized in that, The antifouling material described in S2 is used in environments containing inland river water, seawater, or air, and the adhesion test described in S2 requires 12 hours.

4. The method for testing the antifouling properties of an antifouling material against bioadhesion according to claim 1, characterized in that, The tensile test described in S3 includes the following steps: S31. Clamp the plastic strip and the anti-fouling coating at the top and bottom ends of the tensile testing machine respectively; S32. Set the tensile testing machine to a tensile testing speed of 50 mm / min, stretch the sample after the treatment in S2, and record the maximum stress during the stretching process.

5. The method for testing the antifouling properties of an antifouling material against bioadhesion according to claim 1, characterized in that, The calculation formula for data processing described in S4 is: In the calculation formula, N is the average value of the maximum stress, and S is the area of ​​the adhesion region. Substituting the average value of the maximum stress into the calculation formula, the maximum shear strength K is calculated, and K is the simulated biological slime adhesion strength.

6. The method for testing the antifouling properties of an antifouling material against bioadhesion according to claim 1, characterized in that, The smaller the shear force parameter in S5, where the simulated biofilm adhesion strength is compared to the biofilm's own adhesion strength, the stronger the antifouling material's resistance to bioadhesion; conversely, the larger the parameter, the weaker the antifouling material's resistance to bioadhesion.

Citation Information

Patent Citations

  • A Test Method for the Biofouling Resistance of Antifouling Materials

    CN106501132B